Synthesis and Characterization of Complex Compounds of Tetra-aza Macrocyclic Ligand - Mayura A. Panchbhai; L. J. Paliwal; N. S. Bhave (E-Journal of Chemistry)
This paper deals with the synthesis and characterization of a macrocyclic ligand (L) and its new-fangled complex compounds of the general formula [M-L Cl2] for M= Ru(III), and [M-L] for Pt(II) and Pd(II) where L is a macrocyclic ligand resulted from the condensation reaction of ethylene diamine and ethyl acetoacetate. The ligand and its coordination compounds are formulated according to the chemical analysis, electronic, infrared, 1HNMR and mass spectra, as well as magnetic susceptibility values.